Towards voluntary guidelines for people-centred land-water tenure: the untapped synergies between rights-based land and water governance - van Koppen, Barbara (2015)
Water is absent in the ‘Voluntary Guidelines on the Responsible Governance of Tenure of Land, Fisheries and Forests in the Context of Food Security’ (FAO, 2012). This paper explored whether and how the people-centred approaches and the human rights values that underpin this document can be better applied in the water sector and how more recognition of the land-water interface can support this. This is elaborated for participatory approaches in which people, especially the rural and peri-urban poor, better oversee the many interdependencies of natural resources and their multiple uses than the compartmentalised public sector. Further, human rights values are discussed for the development of land-bound water infrastructure, tracing the upcoming debates about a core minimum water service level that includes small-scale productive uses. Lastly, entitlements to land and to naturally available water resources are compared. While the water sector should replicate the current strong recognition of customary land rights to customary and informal water entitlements, an important difference is discussed as well: states are water regulators in a public interest. In this capacity, they should also to protect water entitlements by the vulnerable in negotiations about large-scale land-based investments through procedural and water prioritization arrangements.